STUDI EKPLORATORIS DAYA TARIK DESTINASI WISATA DI TROWULAN KABUPATEN MOJOKERTO, 2017 - Windy Arista; Ahmad Zafrullah TN.; Firman Rosjadi Djoemadi (CALYPTRA, 2018)
One of the sectors driving economic growth is tourism. The development of tourism has an important role in increasing the absorption of manpower, encouraging the equalization of business opportunity, encouraging the equitable distribution of national development, and contributing to the country's foreign exchange revenue generated from the number of foreign tourists visiting. In this Mojokerto regency aggressively promote tourism in the region, one of which is cultural heritage tourism in Trowulan which has been national standard. This study aims to observe the attractiveness of tourist destinations in Trowulan, the analysis is done by interviewing methods that use 4 components of attraction of tourist destinations (Crouch & Ritchie, 1999) ie Mix of activities, facilitating resources, organization and location. The findings of this study that there is a lack of activity, the gap between organizations and facilities that have not been good if they see the status as a national cultural heritage.